The Head AIS 4+ Injury Thresholds for the Elderly Vulnerable Road User Based on Detailed Accident Reconstructions - Wu, He; Han, Yong; Pan, Di; Wang, Bingyu; Huang, Hongwu; Mizuno, Koji; Thomson, Robert (Frontiers in Bioengineering and Biotechnology, 2021)
Compared with the young, the elderly VRUs (age greater than or equal to 60 years old) face a greater risk of injury or death in a traffic accident. A contributing vulnerability are the ageing processes that affect their brain structure. The purpose of this study was to investigate the injury mechanisms and establish head AIS 4+ injury tolerances for the elderly VRUs based on various head injury criteria. A total of 30 elderly VRUs accidents with detailed injury records and video information were selected and the VRUs’ kinematics and head injuries were reconstructed by combining a multi-body system model (PC-Crash and MADYMO) and the THUMS (Ver. 4.0.2) FE models. Four head kinematic-based injury predictors (linear acceleration, angular velocity, angular acceleration, head injury criteria (HIC), and three brain tissue injury criteria (Coup pressure, maximum principal strain (MPS), and cumulative strain damage measure (CSDM)) were studied. The correlation between injury predictors and injury risk was developed by using logistical regression models for each criterion. The results show that the calculated thresholds for head injury for the kinematic criteria were lower to those reported in previous literature studies. For the brain tissue level criteria, the thresholds calculated in this study were generally similar than those of previous studies with the exception for the coup pressure. The models had higher (>0.8) Area Under Curve (AUC) values for Receiver Operator Characteristics (ROC) indicating good predictive power. This study could provide additional support for understanding brain injury thresholds in elderly people